2008
DOI: 10.1007/s00228-008-0494-6
|View full text |Cite
|
Sign up to set email alerts
|

Women encounter ADRs more often than do men

Abstract: Our data confirm the higher risk of ADRs among female subjects compared with a male cohort. Several explanations were investigated. No single risk factor could be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
132
5
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(168 citation statements)
references
References 39 publications
26
132
5
5
Order By: Relevance
“…[30][31][32][33][34] The subgroup analyses of pooled data showed that the efficacy of suvorexant did not vary as a function of age or gender. With regard to safety, there was no evidence to suggest that any difference in AEs (total number and somnolence) between suvorexant and placebo was more marked in elderly than non-elderly patients.…”
Section: Discussionmentioning
confidence: 96%
“…[30][31][32][33][34] The subgroup analyses of pooled data showed that the efficacy of suvorexant did not vary as a function of age or gender. With regard to safety, there was no evidence to suggest that any difference in AEs (total number and somnolence) between suvorexant and placebo was more marked in elderly than non-elderly patients.…”
Section: Discussionmentioning
confidence: 96%
“…20 The lower risk of error in women is a surprising finding, and is in contrast to findings suggesting that women are at greater risk of adverse drug events. 21 It is possible, however, that GPs are more cautious when prescribing for women, hence the lower risk of error.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Few studies have addressed gender differences in the nocebo effect. Women experience adverse drug reactions more often than do men [53], and evidence suggests that women are more prone to experience nocebo effects [54]. In a study evaluating the SSRI fluoxetine, women reported slightly more nocebo effects than men (38.5% versus 30.1%, p , 0.01) [52].…”
Section: Gender Differences In Placebo and Nocebo Effectsmentioning
confidence: 99%